Peran Sholat dalam Mengatasi Depresi - laela nur, laela (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2023)
Depression is a mental health disorder that affects millions of people worldwide. In recent decades, there has been an increasing trend toward a comprehensive approach to managing depression. Depression is a natural emotional problem. Depression must be treated appropriately and correctly in order to provide therapeutic benefits. One area that is receiving more attention is the role of religious activities, such as prayer, in helping individuals overcome depressive symptoms. Prayer therapy contains messages built on concepts that aim to form a person with character. Prayer is effective in healing someone who suffers from mental disorders such as depression and problems in life. The role of prayer for health is that there are four therapeutic aspects to prayer: the exercise aspect, the meditative aspect, the suggestive aspect, and the joyful aspect. By living a passionate life, we can realize each individual's abilities and potential in a variety of different lifestyles. The goal to be achieved is to develop studies on individuals suffering from mental disorders (depression) so that they become positive individuals for each individual with underlying conditions, as well as the possibility of optimal happiness through prayer. From the role of prayer, a person can overcome the problems faced in life and become a healthy person.